2017
DOI: 10.1007/s10694-017-0652-4
|View full text |Cite
|
Sign up to set email alerts
|

Occupant Tenability in Single Family Homes: Part II: Impact of Door Control, Vertical Ventilation and Water Application

Abstract: Abstract. This paper describes experimental investigations of fire service ventilation and suppression practices in full-scale residential structures, including a one-story, 112 m 2 , 3 bedroom, 1 bathroom house with 8 total rooms and a two-story 297 m 2 , 4 bedroom, 2.5 bathroom house with 12 total rooms. The two-story house featured a modern open floor plan, two-story great room and open foyer. Seventeen experiments were conducted varying fire location, ventilation locations, the size of ventilation openings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…This manuscript focuses on occupant exposures from the fire prior to ventilation and flashover did not occur in this timeframe (though flashover did occur after ventilation). Part II will analyze conditions after fire service ventilation [20]. Bedroom 1 in both houses was furnished with a queen bed comprised of a mattress, box spring, wood frame, two pillows and comforter.…”
Section: Fuel Loadmentioning
confidence: 99%
“…This manuscript focuses on occupant exposures from the fire prior to ventilation and flashover did not occur in this timeframe (though flashover did occur after ventilation). Part II will analyze conditions after fire service ventilation [20]. Bedroom 1 in both houses was furnished with a queen bed comprised of a mattress, box spring, wood frame, two pillows and comforter.…”
Section: Fuel Loadmentioning
confidence: 99%
“…Each of these studies was focused on a specific fire service tactic and simulated those tactics in a controlled manner to examine the impact on the fire environment. In 2017, Traina et al [9] examined the impact of firefighter transitional attack on occupants during a series of vertical ventilation experiments. They concluded that transitional attack was able to reduce the thermal fractional effective rate (FER) by 1/5 in a ranch home geometry 60 s after water application.…”
Section: Introductionmentioning
confidence: 99%
“…Similar conclusions about the effectiveness of a closed door have been arrived at in other experimental studies that have focused on concentrations of CO, CO 2 , O 2 , and water vapor. 1,[42][43][44] This work provides the first report of the effect of residential bedroom door position on HCN concentration. Together with CO, CO 2 , and O 2 concentration measurements, this new approach to quantify HCN concentration in live-fire experiments can provide a more complete understanding of the risks and possible protective measures for occupants trapped in residential fire environments.…”
Section: Application In Full-scale Live Fire Experimentsmentioning
confidence: 86%